History, status, and future challenges of hydrogen energy in the transportation sector - Wen-Long Shang; Xuewang Song; Qi Liao; Meng Yuan; Jie Yan; Yamin Yan (Asian Development Bank Institute (ADBI), 2023)
In recent years, extreme weather around the world due to climate change has occurred increasingly frequently, and countries globally have gradually realized the harm caused by global warming. All countries are also making efforts to promote less consumption of fossil fuel energy and the use instead of renewable energy technologies that are environmentally friendly and have lower carbon emissions. The transportation sector, as a main contributor to energy consumption and pollution emissions, is receiving increasing attention. At the same time, new energy vehicles are more energy efficient and environmentally friendly than fuel vehicles, making them more prevalent in the automotive market, which is flourishing. Green hydrogen energy can be used as a renewable, clean, and efficient energy source for new energy vehicles and is also gradually being used in transportation to promote the goal of carbon neutrality. This paper reviews the research on hydrogen energy in the transportation field, summarizes the previous research results, and presents the challenges to the future application of hydrogen energy.
Keywords: R40; 330; carbon neutrality; hydrogen; climate change; renewable energy; transportation